DYNAMICS OF CHILD DEVELOPMENT OF MADRASAH AGE IN THE CONTEXT OF EDUCATION - Millatus Shofi; Hisyam Maulana; Hammam Harits A.; Vina Muniroh; Siti Anisa (AL KAYYIS, 2024)
Educational Patterns that aim to understand the dynamics of school-age children's development in the context of learning. The main focus lies on the cognitive, emotional, and social development of children aged 7–12 years and their interactions with instructional strategies and the learning environment. The approach used is the library research method. The results of the study indicate that optimal learning is achieved when teachers adjust learning methods to the child's developmental stage. Emphasis is placed on active learning, scaffolding, and social-emotional support. The conclusion of this literature study is that understanding the characteristics of child development greatly contributes to the effectiveness of learning, especially at the elementary education level in this case, madrasah children.